2007
DOI: 10.1111/j.1475-3588.2007.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Service Use for Mental Health Problems Among British Schoolchildren

Abstract: Background:  Most previous studies of service use in relation to mental health have examined services in the USA. We wanted to provide up‐to‐date findings from a general population sample of British schoolchildren. Method:  A total of 2461 children aged 5–15 from the 1999 British Child and Adolescent Mental Health Survey were followed up for 3 years. We examine the relationship between a wide variety of potential predictors gathered in 1999 and the use of services over the following 3 years. Results:  Contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
94
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 57 publications
9
94
1
3
Order By: Relevance
“…However, in adjusted analyses, neither ADHD nor the presence of associated comorbid symptoms predicted service use. The lack of association with comorbid symptoms and parental perception of burden is in contrast to other literature [7,[22][23][24][25][26]28]. The main concurrent predictor of service use was a higher level of parental mental health problems.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, in adjusted analyses, neither ADHD nor the presence of associated comorbid symptoms predicted service use. The lack of association with comorbid symptoms and parental perception of burden is in contrast to other literature [7,[22][23][24][25][26]28]. The main concurrent predictor of service use was a higher level of parental mental health problems.…”
Section: Discussioncontrasting
confidence: 54%
“…This finding contributes to the literature as other studies have not found this association in analyses that adjust for child-level clinical factors [7,24,28,29]. It is possible that some differences in findings across studies might relate to differences in study design, this study reflecting a case-control comparison of service users and non-users nested within a long-term follow-up study.…”
Section: Discussionmentioning
confidence: 50%
“…associated with use of different services suggesting that the allocation of children and families to different types of services may have been largely random, with a need of rational protocols to improve access and cost-effective use of resources. An earlier study found that parental concern along with severity of child psychopathology and co-morbidity were related to multiple services contact [8]. Parents in this study identified several barriers to services.…”
Section: Discussionmentioning
confidence: 86%
“…Parental perception of their child's mental health status as problematic or burdensome is thus an important factor in conceptualizing and planning service pathways and protocols [1,25]. The British longitudinal study found that contact with most services for mental health problems was predicted by the impact of psychopathology; contact with teachers or primary health care; and parents' and teachers' perception that the child has significant difficulties [5,8]. When this research question was, however, re-examined over a longer period of 4 years, future referrals to specialist child mental health services were predicted by symptom severity rather than parental burden [25].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of emotional and behavioural problems in children and adolescents is a priority issue not only for public health policy, but also in the context of clinical practice and research. Nevertheless, and despite the efforts in early detection, different research studies have suggested that only a minority of the adolescent population with needs in the area of mental health comes in direct contact with specialized services [8,9].…”
mentioning
confidence: 99%